Biodiversity of parasites in a freshwater environment with respect to pollution: metazoan parasites of chub (Leuciscus cephalus L.) as a model for statistical evaluation - Dusek, L; Gelnar, M; Sebelová, S (International journal for parasitology, 1998)
This paper represents an attempt to evaluate the environmental indicative potential of the biodiversity of monogenean parasites using hierarchically structured species-abundance data. A logical set of statistical methods integrating standard diversity indices, a novel approach to quantitative analysis of cumulative species-abundance curves and species-abundance models was applied for this purpose. Applicability of biodiversity measures was demonstrated using experimental data from a 1-year study on the ecology of metazoan parasites of chub (Leuciscus cephalus) in one polluted and one control site in the Morava river, Czech Republic. Analyses at the component community level revealed a significant decrease in the number of parasite species with a more equal distribution of their abundances in the polluted site compared with the control site. In order to reach a better understanding of the changes, diversity of Monogenea as a dominant part of the community was further examined within categories of species created according to: (1) specificity of infection (specialists and generalists), (2) monogenean genera (Dactylogyrus, Gyrodactylus and Paradiplozoon) and (3) inhabited guilds (skin + fins, gills). Assemblages of specialists in the polluted site exhibited a significantly reduced species richness and unequal distribution of abundances. The opposite pattern was observed in the case of generalists. The influence of pollution was also reflected by the distribution of species abundances within communities of Dactylogyrus and Paradiplozoon, while no significant shift was identified in the genus Gyrodactylus.
Keywords: stochastické procesy; Fresh Water; ekosystém; Population Density; znečištění vody; cestodózy; Trematode Infections; sladká voda; Cyprinidae; hustota populace; Models, Biological; zvířata; nemoci ryb; Stochastic Processes; Species Specificity; Trematoda; biologické modely; Cestoda; Fish Diseases; druhová specificita; Cestode Infections; Water Pollution; Ecosystem; infekce červy třídy Trematoda; Animals